When Food Meets Price: Drivers of Revisit Intention in Bandung’s Café Scene - Natanael, Johanes; Yuliantoro, Nonot; Kurniawan, Johannes (Jurnal Ilmiah Global Education, 2025)
This study explores the influence of food quality and perceived price on revisit intention within the context of Khoe Pek Goan Bloemenstad Café in Bandung. As the culinary industry in Bandung becomes increasingly competitive, understanding the key determinants of customer loyalty is crucial for sustaining business growth. Employing a descriptive quantitative approach, the research gathers insights from café patrons through structured online questionnaires and analyzes the data using structural equation modeling. The findings reveal that both food quality and perceived price play significant roles in shaping customers’ intention to return. The study highlights the importance of delivering consistent taste, freshness, and visually appealing presentation, alongside pricing strategies that reflect perceived value. A distinguishing feature of this research is its integration of customer loyalty theory with real-world operational insights, including menu engineering practices. The results offer practical implications for café managers seeking to enhance customer retention, while also contributing to academic discourse on consumer behavior in the food and beverage sector.